Multicultural Islamic Education in Indonesia: The Urgency Value of Model and Method - Ulfa, Ulfa; C.H., Mufidah; Susilawati, Samsul; Barizi, Ahmad (ADDIN, 2022)
The academic problems in this research study are multicultural Islamic education, which begins from academic anxiety that multicultural Islamic education development has not been implemented optimally. It is because Islamic education is often impressed as an education social fabrication system that is dogmatic, doctrinal, monolithic, and does not have a multicultural perspective. Meanwhile, the fact is that the position of Islamic education in developing dialogue with the community is very strategic since the fundamental of Islamic education is rahmatan lil 'alamiin, which can hold various aspects of life. It is a literature qualitative research with a documentary review and data analysis which uses three plots of activities that occur simultaneously, that are data reduction, data presentation, conclusion drawing, or verification. The findings of this study include the theoretical level of the conceptualization of multicultural education by synthesizing western thoughts to be led to a map of Islamic thought, so as to produce methods, values, and the urgency of multicultural education on the basis of Islamic theology. Namely unity in the divine aspect and its message (revelation), prophetic unity, no compulsion in religion, and recognition of the existence of other religions. This research also found the essence of multiculturalism as a frame model for Islamic education, as well as the appropriate multicultural Islamic education method to be applied in Indonesia. These values include: unity of humankind, competition in good works, forgiveness toward humankind, living together, equality/egilitarianism, mutual understanding, mutual respect, trust, positive thinking, tolerance, and non-violence. The implications of the results of this research are to provide recommendations that the reconstruction of the multicultural Islamic education model is related to the relationship between Muslims and non-Muslims by using learning theory that is relevant to the dynamics of the times and the diversification of religious communities in Indonesia.